Uso de combinação de coquetel de meio t80/40lh + staff para a cultura de estirpes leptospirais do sorogrupo Sejroe - Brasil, T.; Loureiro, A. P.; Correia, L.; Cabral, B.; Pereira, P. V.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Bovine leptospirosis is an infectious-contagious disease of worldwide distribution, endemic in tropical countries. Correlation between reproductive problems and Leptospira infection has been demonstrated, especially for strains of serogroup Sejroe. However, culturing those strains from bovine clinical samples is still challenging, since it is laborious and demands expertise.